Quo Vadis, Musica? Artistic Mission and Duty in the Context of the Third Millennium - Golema, Amelia. Redakcja (Akademia Muzyczna im. Karola Lipińskiego we Wrocławiu, 2025)
Where is music heading? Is its destination clearly defined? Who determines its goals? What is the quality and sense of 21st-century music? What does it mean to be an artist? In today’s world marked by ambiguity, which overwhelms us with excess of information and a cocktail of sounds that are increasingly difficult to filter or verify, there is often no time or space for pondering the important questions. The publication is an attempt to reflect the melting pot of contem-porary music. It refers to Polish and foreign music, to the past and the present, to areas that lie on the borderline between social sci-ences, humanities, and musical art. Among the authors, there are theorists and performers, professors as well as students. They are united, however, by a passion for music, which for them is a way of life and a means of self-expression, and which in the world of rapidly developing artificial intelligence, fortunately, still remains a human domain.
Keywords: Artistic Identity; Polish Composers; Musical Heritage in Wrocław